2003
DOI: 10.1046/j.1365-3148.2003.00412.x
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐Ce complicating two consecutive pregnancies with increasing severity of haemolytic disease of the newborn

Abstract: The Ce antigen is expressed on red cells of individuals with Rh haplotypes, R1 or CDe and r' or Cde. However, anti-Ce is rare, and only two cases of severe haemolytic disease of the newborn (HDN) caused by this antibody have been described (Malde et al., 2000; Wagner et al., 2000). We describe a woman who was found to have anti-Ce in her second pregnancy, resulting in a neonate with HDN that required exchange transfusion. She subsequently had a twin pregnancy, where both the twins were affected by severe haemo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Fortunately, in our case there were no signs of HDFN in none of the two neonates delivered by Caesarean section at 36 weeks of gestation. It is worth mentioning that anti‐Ce cases could be misidentified as anti‐C and hence underreported (Malde et al ., ; Ranasinghe et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Fortunately, in our case there were no signs of HDFN in none of the two neonates delivered by Caesarean section at 36 weeks of gestation. It is worth mentioning that anti‐Ce cases could be misidentified as anti‐C and hence underreported (Malde et al ., ; Ranasinghe et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…This is in accordance with blood donor deferral rates found in the literature, which range from 3% to 15%. [10–12] In a blood donation program where the majority of blood donors were first time donors it is also a reflection of the prevalence of anemia in the adult population in the community. The prevalence of anemia in our study population was much lower than reported in our general population (1.8% vs 25%),[13] probably as majority of our donors are adult males (males, 98.3%; females, 1.7%).…”
Section: Discussionmentioning
confidence: 99%
“…• Severe HDFN-anti-D and anti-c [31,32] • Mild disease-anti-C, anti-E, and anti-e [33][34][35][36][37] 6.1.1 D antigen and antibodies…”
Section: Rh Blood Group Systemmentioning
confidence: 99%
“…Anti-e is usually a very rare cause of HDN; the disease is usually mild [68]. In addition to the above antibodies, there are many other antibodies belonging to Rh family which are associated with HDFN [35,69,70]. Table 3.…”
Section: Anti-c Anti-e Anti-e and Othersmentioning
confidence: 99%